2014
DOI: 10.1371/journal.pone.0087470
|View full text |Cite
|
Sign up to set email alerts
|

Driving with Binocular Visual Field Loss? A Study on a Supervised On-Road Parcours with Simultaneous Eye and Head Tracking

Abstract: Post-chiasmal visual pathway lesions and glaucomatous optic neuropathy cause binocular visual field defects (VFDs) that may critically interfere with quality of life and driving licensure. The aims of this study were (i) to assess the on-road driving performance of patients suffering from binocular visual field loss using a dual-brake vehicle, and (ii) to investigate the related compensatory mechanisms. A driving instructor, blinded to the participants' diagnosis, rated the driving performance (passed/failed) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
132
3
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(167 citation statements)
references
References 44 publications
(62 reference statements)
12
132
3
6
Order By: Relevance
“…Importantly, the observed differences in detection performance between the HP and LP group could not be explained by age, sex, handedness, video game experience, holding of a driver's license, years of driving experience, time between brain lesion and examination, or side and extent of the homonymous visual field defect, since we did not find significant differences for any of these variables between the groups. The little relevance of the extent of a visual field defect for driving performance has previously been demonstrated [8,14,27]. Despite obvious differences in the detection rate, both patient groups exhibited significantly longer reaction times to obstacles presented in their blind field compared to the Co group's reaction times to obstacles presented in the right hemifield.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Importantly, the observed differences in detection performance between the HP and LP group could not be explained by age, sex, handedness, video game experience, holding of a driver's license, years of driving experience, time between brain lesion and examination, or side and extent of the homonymous visual field defect, since we did not find significant differences for any of these variables between the groups. The little relevance of the extent of a visual field defect for driving performance has previously been demonstrated [8,14,27]. Despite obvious differences in the detection rate, both patient groups exhibited significantly longer reaction times to obstacles presented in their blind field compared to the Co group's reaction times to obstacles presented in the right hemifield.…”
Section: Discussionmentioning
confidence: 78%
“…Surely, though, as opposed to actual driving, participants in our study did not have to perform such driving tasks as merging into floating traffic, requiring additional head movements to check for other traffic at the side and back of one's own vehicle. Reconciling divergent evidence for the importance of either eye or head movement in compensatory visual search behavior of patients with HH, Kasneci and colleagues [27], employing quantitative analyses of both eye and head movements in an onroad test, found that both increased eye and head movements into the blind hemifield contributed to successfully passing a driving test.…”
Section: Discussionmentioning
confidence: 99%
“…Future studies may wish to consider whether these participants are using certain strategies to help improve their vigilance when detecting hazards or driving. Some patients may compensate for their visual deficit by using more effective scanning strategies when driving,25 a finding that has also been reported when considering other visual tasks 26 27. We, therefore, plan to investigate whether compensatory eye movement changes may have helped some participants to overcome hazard perception impairment.…”
Section: Discussionmentioning
confidence: 80%
“…Details on data collection can be found in Kasneci et al (2014a), Kübler et al (2015a), and Kübler et al (2015b). Aim of these studies was to investigate the relationship between binocular visual field defects, eye movements, and driving performance.…”
Section: Driving With Visual Field Defectsmentioning
confidence: 99%